Pressurized formic acid dehydrogenation: an entropic spring replaces hydrogen compression cost. Issue 23 (1st November 2022) - Do, Van K.; Alfonso Vargas, Nicolas; Chavez, Anthony J.; Zhang, Long; Cherepakhin, Valeriy; Lu, Zhiyao; Currier, Robert P.; Dub, Pavel A.; Gordon, John C.; Williams, Travis J.
Abstract : Several catalysts are shown to evolve useful H2 pressure from formic acid dehydrogenation, to replace compression cost with reaction entropy. Many of them rely on trace CO to initiate effectively. Mechanistic rationale and applications are discussed. Abstract : Formic acid is unique among liquid organic hydrogen carriers (LOHCs), because its dehydrogenation is highly entropically driven. This enables the evolution of high-pressure hydrogen at mild temperatures that is difficult to achieve with other LOHCs, conceptually by releasing the "spring" of energy stored entropically in the liquid carrier. Applications calling for hydrogen-on-demand, such as vehicle filling, require pressurized H2 . Hydrogen compression dominates the cost for such applications, yet there are very few reports of selective, catalytic dehydrogenation of formic acid at elevated pressure. Herein, we show that homogenous catalysts with various ligand frameworks, including Noyori-type tridentate (PNP, SNS, SNP, SNPO), bidentate chelates (pyridyl)NHC, (pyridyl)phosphine, (pyridyl)sulfonamide, and their metallic precursors, are suitable catalysts for the dehydrogenation of neat formic acid under self-pressurizing conditions. Quite surprisingly, we discovered that their structural differences can be related to performance differences in their respective structural families, with some tolerant or intolerant of pressure and others that are significantly advantaged by pressurized conditions. We further find important roles for H2 and CO in catalyst activation and speciation. In fact, for certain systems, CO behaves as a healing reagent when trapped in a pressurizing reactor system, enabling extended life from systems that would be otherwise deactivated.